Distribution and Biology of Bull Trout (Salvelinus confluentus) in the Mackenzie Valley, Northwest Territories, with Notes on Sympatry with Dolly Varden (Salvelinus malma) + Online Appendix 1 (See Article Tools) - Mochnacz, Neil J.; Bajno, Rob; Reist, James D.; Low, George; Babaluk, John A. (ARCTIC, 2013)
Streams were surveyed along the Mackenzie Valley, Northwest Territories, to investigate the distribution and biology of riverine char. Bull trout (Salvelinus confluentus) were captured in 24 of 43 streams sampled from three watersheds: the Kotaneelee River, the South Nahanni River, and the Central Mackenzie Mountains. The first confirmed sympatric bull trout and Dolly Varden (Salvelinus malma) populations in the Northwest Territories are reported from the Gayna River (~65˚17′ N, 129˚21′ W). This location represents a geographical range extension for bull trout approximately 200 km northwest of the previous northernmost published location in the central Northwest Territories (~64˚30′ N and 125˚00′ W, Great Bear River). It also extends the geographical range of Dolly Varden south approximately 300 km from the closest known populations located in the Peel River basin. The identification of this geographic range expansion is a result of extending both our sampling range and our ability to identify riverine chars accurately. In bull trout, we observed two different growth patterns, which correspond to non-migratory and migratory life histories. Northern bull trout populations are relatively small and widespread, and they are separated from one another by large distances and in some cases by natural barriers. Although these populations share similar biological traits with their southern counterparts, the northern fish mature later and do not spawn as often, which increases their sensitivity to exploitation and other anthropogenic perturbations. Des cours d’eau du long de la vallée du Mackenzie, dans les Territoires du Nord-Ouest, ont fait l’objet d’un relevé visant à étudier la répartition et la biologie des ombles fluviaux. Des ombles à tête plate (Salvelinus confluentus) ont été capturés dans 24 des 43 cours d’eau échantillonnés à partir de trois bassins hydrographiques : la rivière de Kotaneelee, la rivière Nahanni Sud et les monts Mackenzie centraux. Les premières populations sympatriques confirmées d’ombles à ...